Two Trials for Witchcraft - Murray, Margaret A (Proceedings of the Society of Antiquaries of Scotland, 1922)
Many objections have been raised as to the value of the evidence given by witches. It is argued that a questionary was drawn up by the inquisitors and used by all witch-hunters, hence the similarity in the accounts. Records of two trials are presented in full: Alexander Hamilton in Edinburgh, 1630 and Lillias Adie in Torryburn, 1704.